Impacts of environmental filters on functional redundancy in riparian vegetation. Issue 3 (29th February 2016) - Bruno, Daniel; Gutiérrez‐Cánovas, Cayetano; Sánchez‐Fernández, David; Velasco, Josefa; Nilsson, Christer
Summary: Understanding and predicting ecosystem responses to multiple environmental pressures is a long‐standing interest in ecology and environmental management. However, few studies have examined how the functional features of freshwater biological communities vary along multiple gradients of environmental stress. Furthermore, modelling these functional features for a whole river network constitutes a strong potential basis to improve ecosystem management. We explored how functional redundancy of biological communities (FR, a functional feature related to the stability, resistance and resilience of ecosystems) responds to single and multiple environmental filters. We compared these responses with those of functional richness, evenness and divergence. We used riparian vegetation of a Mediterranean basin, and three of the main environmental filters affecting freshwater communities in such regions, that is drought, flow regulation and agricultural intensity, thus considering the potential effect of natural environmental variability. We also assessed the predictability of FR and estimated it for the entire river network. We found that all functional measures decreased with increasing environmental filter intensity. However, FR was more sensitive to single and multiple environmental filters compared to other functional measures. The best‐fitting model explained 59% of the FR variability and included agriculture, drought and flow regulation and the pairwise interactions of agriculture with drought and flow regulation. The parameters of the FR models differed from null model expectations reflecting a non‐random decline along stress gradients. Synthesis and applications . We found non‐random detrimental effects along environmental filters' gradients for riparian functional redundancy (the most sensitive functional index), meaning that increased stress could jeopardize stability, resistance and resilience of these systems. In general, agriculture caused the greatest impact on functional redundancy and functional diversity measures, being the most important stressor for riparian functionality in the study area. Temporary streams flowing through an agricultural, regulated basin had reduced values of functional redundancy, whereas the free‐flowing medium‐sized, perennial water courses flowing through unaltered sub‐basins displayed higher values of functional redundancy and potentially greater stability against human impacts. All these findings along with the predicted basin‐wide variation of functional redundancy can assist environmental managers in improving monitoring and ecosystem management. Abstract : We found non‐random detrimental effects along environmental filters' gradients for riparian functional redundancy (the most sensitive functional index), meaning that increased stress could jeopardize stability, resistance and resilience of these systems. In general, agriculture caused the greatest impact on functional redundancy and functional diversity measures, being the most important stressor for riparian functionality in the study area. Temporary streams flowing through an agricultural, regulated basin had reduced values of functional redundancy, whereas the free‐flowing medium‐sized, perennial water courses flowing through unaltered sub‐basins displayed higher values of functional redundancy and potentially greater stability against human impacts. All these findings along with the predicted basin‐wide variation of functional redundancy can assist environmental managers in improving monitoring and ecosystem management.